2022
DOI: 10.26434/chemrxiv-2022-3md3n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do large language models know chemistry?

Abstract: Mostly yes. We systematically evaluate machine learning large language models (LLMs) that generate code in the context of chemistry. We produce a benchmark set of problems, and evaluate these models based on correctness of code by automated testing and evaluation by experts. We find recent LLMs are able to write correct code across a variety of topics in chemistry and their accuracy can be increased by 30 percentage points via prompt engineering strategies, like putting copyright notices at the top of files. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…AI tools that can autoformalize the informal scientic literature, generate novel theories, and auto-complete complex proofs could open new avenues for automating theory discovery. LLMs have demonstrated capabilities in solving chemistry problems, 90,91 as well as answering scientic question-and-answer problems invoking quantitative reasoning. 92 However, LLMs are unreliable they famously "hallucinate" (generate falsehoods) and are biased or unreliable evaluators of their own outputs.…”
Section: Discussionmentioning
confidence: 99%
“…AI tools that can autoformalize the informal scientic literature, generate novel theories, and auto-complete complex proofs could open new avenues for automating theory discovery. LLMs have demonstrated capabilities in solving chemistry problems, 90,91 as well as answering scientic question-and-answer problems invoking quantitative reasoning. 92 However, LLMs are unreliable they famously "hallucinate" (generate falsehoods) and are biased or unreliable evaluators of their own outputs.…”
Section: Discussionmentioning
confidence: 99%
“…It works well for the defined downstream predictive task, especially demonstrating improved performance in small data settings. The question of whether large language models, such as GPT-3, trained on non-chemical corpora, can acquire meaningful knowledge in the field of chemistry has also been investigated in a recent study 40 .…”
Section: Transfer Learning In Olfactionmentioning
confidence: 99%
“…NLP algorithms have exciting potential for chemistry applications; for example, voiceactivated, hands-free software could be used to read and write electronic notebooks while performing experiments. In computational chemistry, vocal prompts could be used to input the commands or as support for programming tasks; Hocky, White, and colleagues (93,94) recently showed that Codex (95) can generate code for chemical applications from natural language prompts. Further applications of NLP in chemistry are certainly promising.…”
Section: Speech Recognitionmentioning
confidence: 99%